PSYCHOLOGICAL FACTOR ANALYSIS OF HEALTH SERVICE SELECTION DECISIONS IN OUTPATIENTS INSTALLATION BHAYANGKARA BANJARMASIN HOSPITAL - Kristina Dewi; Sri Hartini (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Bhayangkara Hospital is a hospital within the National Police that organizes police medical service activities to support the operational tasks of the Police and police health services, data on outpatient visits of POLRI civil servants to Bhayangkara Tk III Hospital Banjarmasin in 2019 amounted to 5.21% and decreased to 4.18% in 2020. The main factors that influence consumers make decisions include psychological factors. Purpose: The purpose of this study was to analyse psychological factors related to the selection of outpatient health services at Bhayangkara Tk III Hospital Banjarmasin. Methods: This research is an analytical observational study with a cross-sectional design. The population of this study was outpatient civil servants at the National Police, the sample size of this study was 100 respondents, using simple random sampling technique. The data were collected by using a questionnaire, the data analysis used was descriptive and multiple linear regression. Results: The results of this study indicate that perceptions (p = 0.000) and attitudes (p = 0.001) partially significantly influence the decision to choose outpatient health services at Bhayangkara Tk III Hospital Banjarmasin, while motivation and learning variables have no effect. Figure R Square 0.386, shows 38.6% of the decision to choose outpatient health services is influenced by psychological factors which include motivation, perception, learning and attitudes. The perception factor is the dominant factor influencing the decision to choose outpatient health services Conclusion: Psychological factors of patient have an influence on the decision to choose outpatient health services at Bhayangkara Tk III Hospital Banjarmasin